Consumer interaction towards content marketing in social media pages (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research deals with the study of content marketing in social media pages with the development of modern marketing methods and the innovation of various methods of promotion adopted by companies to market their products and services. It aims to determine the extent of consumer interaction towards content marketing on social networking pages. A field study was conducted on a random sample in the city of Baghdad from users. Telecommunications companies: Zain Company is a model consisting of (180) male and female users of Zain Iraq Telecommunications Company. The questionnaire was used as a measurement tool, and the research reached several results, the most important of which is that the most used methods in content marketing are text and images, and celebrities are used as influencers to promote their goods and services. The company publishes content that meets the needs and desires of the audience. The content provides the information that customers need about the company’s services. The content also contributed to strengthening the brand. The results show that content through social media sites presents a positive mental image of the company’s services to the consumer, and there is diversity in the use of social media. Social and innovation in marketing content.